1988
DOI: 10.1111/j.1476-5381.1988.tb11661.x
|View full text |Cite
|
Sign up to set email alerts
|

Opioid modulation of non‐cholinergic neural bronchoconstriction in guinea‐pig in vivo

Abstract: 1 Opioid receptors have been demonstrated on sensory fibres in the vagus nerve. Non-cholinergic (NC) neural bronchoconstriction in guinea-pig is due to release of neuropeptides from sensory nerve endings. We have therefore studied the effect of opioids on this NC bronchoconstriction in the anaesthetized guinea-pig. 2 Bilateral vagal stimulation (5 V, 5 ms, 10 Hz) caused reproducible bronchoconstriction in guineapigs which was reduced by atropine (1 mgkg 1), but the NC component was unaffected by hexamethonium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 27 publications
5
33
0
1
Order By: Relevance
“…However, from the results of the present study it is not possible to be certain that p-opioid receptors were involved, as b-and K-opioid receptor agonists were not used, and naloxone is not totally specific for p-receptors. The data are analogous to the results obtained by Belvisi et al (1988), who stimulated retrogradely the afferent vagal nerve fibres in the anaesthetized guinea-pig. The site of these inhibitory effects was peripheral, since the spinal cord and brain stem had been destroyed by pithing.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, from the results of the present study it is not possible to be certain that p-opioid receptors were involved, as b-and K-opioid receptor agonists were not used, and naloxone is not totally specific for p-receptors. The data are analogous to the results obtained by Belvisi et al (1988), who stimulated retrogradely the afferent vagal nerve fibres in the anaesthetized guinea-pig. The site of these inhibitory effects was peripheral, since the spinal cord and brain stem had been destroyed by pithing.…”
Section: Discussionsupporting
confidence: 71%
“…Grundstrom et al, 1984;Karlsson et al, 1984;Frossard & Barnes, 1987), and some have been performed in anaesthetized guinea-pigs, in which vagal afferent nerves were stimulated in retrograde fashion (e.g. Grundstrom & Andersson, 1985;Belvisi et al, 1988). The present study demonstrated that non-cholinergic airways constriction can also be elicited by stimulation of the spinal cord in pithed guinea-pigs.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Opioids inhibit the NANC constrictor response in the guinea-pig in vivo and in the guinea-pig bronchi in vitro (Frossard & Barnes, 1987;Bartho et al, 1987;Belvisi et al, 1988) by preventing release of tachykinins, probably via a y-opioid receptor on airway afferent nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Morphine and opioid peptides inhibit neurally-mediated broncho-constriction (Frossard & Barnes, 1987;Bartho et al, 1987;Belvisi et al, 1988) and plasma exudation (Belvisi et al, 1989) in guinea-pig airways, and mucus secretion in human bronchi by blocking the release of tachykinins from capsaicin-sensitive sensory nerves. Opioids have also been shown to inhibit the cholinergic component of airway excitation in guinea-pigs (Johansson et al, 1989;Belvisi et al, 1990).…”
Section: Introductionmentioning
confidence: 99%